CONTROVERSIAL ISSUES OF SUBSUMPTION OF MALFEASANCE - E. E. Zabuga (Правоприменение)
The subject. The article deals with subsumption of malfeasance, judicial characterization of such white-collar crimes.The purpose of the paper is to answer the question of admissibility of qualification of ho-mogeneous actions of a person according to two separate art. 285 and 286 of the Criminal Сode of the Russian Federation.The methodological basis of the research includes general-scientific methods (analysis and synthesis, system-structural approach) as well as academic methods (formal-legal method, method of interpretation of normative legal and judicial acts).Results and scope of application. Within the meaning of paragraph 15 of the Resolution of Plenum of Supreme Court of the Russian Federation, it is absolutely clear that legal actions of an official, which were not caused by official necessity, must be qualified under art. 285 of the Criminal Code of the Russian Federation.Not only legally, but even from the point of view of ordinary logic, the qualification of ho-mogeneous actions by different criminal law norms is unacceptable.Due to the fact that art. 286 of the Criminal Code of the Russian Federation is not a crime of corruption by its characteristics, art. 285 of the Сriminal Сode of the Russian Federation cannot be regarded as a special case of abuse of power.Conclusions. This is unacceptable to qualify the homogeneous actions of a person according to two separate articles – art. 285 and 286 – of the Criminal Сode of the Russian Federation. It is necessary to add the Resolution of Plenum of Russian Supreme Court from October 16, 2009, No. 19 by the provisions more specifically delimiting qualification of malfeasance crimes according to art. 285 and 286 of the Criminal Сode of the Russian Federation.